2022
DOI: 10.58872/lensa.v16i1.29
|View full text |Cite
|
Sign up to set email alerts
|

Peran Kepuasan Pelanggan Dalam Memediasi Pengaruh Kualitas Produk Terhadap Loyalitas Pelanggan

Abstract: This study aims to analyze the effect of product quality on customer loyalty either directly or through mediation of customer satisfaction. Causality design is used to determine the causal relationship between research variables with a quantitative research approach. Purposive sampling technique was used to determine the research sample in order to obtain as many as 110 Renault customers in PT Maxindo Mobil Indonesia BSD Tangerang. Data analysis was carried out using path analysis with SPSS version 26 program.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
0
0
1

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 1 publication
1
0
0
1
Order By: Relevance
“…The results of this study identified that, brand image cannot create or increase consumer loyalty. This is in accordance with research conducted by Dimyati andSubagio (2016), Firanazulah et al (2021), Ramadhani and Nurhadi (2022), Kasturi et al (2019), andWahyudi et al (2022) the results of the study can be concluded that brand image has a positive and insignificant effect on consumer loyalty.…”
Section: The Effect Of Brand Image On Consumer Loyaltysupporting
confidence: 91%
“…The results of this study identified that, brand image cannot create or increase consumer loyalty. This is in accordance with research conducted by Dimyati andSubagio (2016), Firanazulah et al (2021), Ramadhani and Nurhadi (2022), Kasturi et al (2019), andWahyudi et al (2022) the results of the study can be concluded that brand image has a positive and insignificant effect on consumer loyalty.…”
Section: The Effect Of Brand Image On Consumer Loyaltysupporting
confidence: 91%
“…Dengan kata lain, ketika konsumen merasa bahwa citra merek tersebut memiliki nilai merek yang tinggi maka dapat memiliki persepsi resiko yang lebih rendah, karena pada saat yang sama konsumen sudah memiliki persepsi positif terhadap merek dan meningkatkan niat pembelian yang tinggi. Hal ini menunjukan ketika suatu merek memiliki ekuitas merek yang tinggi maka bisa menjadi tolak ukur seseorang konsumen dalam mengambil keputusan [14].…”
Section: Pendahuluanunclassified